The Improving Injury Prevention in Sports in the Jaw and Maxillary Area: A Comprehensive Overview of Mouthguards and Their Effectiveness - Rusiecka, Amelia; Górniak, Aleksandra; Widawski, Michał; Sobczyk, Aleksander; Kubas, Aleksandra; Gizińska, Natalia; Lewandowska, Paulina (Quality in Sport, 2025)
Mouthguards, also referred to as mouth protectors or intraoral protective devices, are designed to safeguard teeth and surrounding soft tissues from injury during sports activities. Typically made from materials such as EVA, acrylics, silicone, and polyurethane, mouthguards play a vital role in preventing dental trauma, including tooth fractures, luxation, soft tissue damage, and jaw injuries. Custom-made variants, particularly those created through digital workflows and 3D printing, offer improved comfort, occlusal fit, and protective efficiency, with ongoing advancements promising further enhancements through biocompatible, rubber-like materials. Proper occlusal adjustment, such as flat grinding, enhances contact and comfort, contributing to better user compliance. Research suggests custom mouthguards not only offer superior protection compared to over-the-counter options but may also positively influence athletic performance, including balance and muscle activation through mechanisms like concurrent activation potentiation. Despite their benefits, cost and accessibility remain barriers to widespread use. Thus, custom-made mouthguards are strongly recommended for athletes engaged in high-impact sports to ensure optimal protection and performance support.